Acidity-responsive nanoplatforms aggravate tumor hypoxia via multiple pathways for amplified chemotherapy. (May 2023) - Yin, Jiajia; Wang, Chenxi; Zhao, Lei; Xu, Kang; Guo, Yuxin; Song, Xuejiao; Shao, Jinjun; Xu, Huae; Dong, Xiaochen
Abstract: Since the hypoxia tumor microenvironment (TME) will not only limit the treatment effect but also cause tumor recurrence and metastasis, intratumoral aggravated hypoxia level induced by vascular embolization is one of the major challenges in tumor therapy. The chemotherapeutic effect of hypoxia-activated prodrugs (HAPs) could be enhanced by the intensified hypoxia, the combination of tumor embolization and HAP-based chemotherapy exhibits a promising strategy for cancer therapy. Herein, an acidity-responsive nanoplatform (TACC NP) with multiple pathways to benefit the hypoxia-activated chemotherapy is constructed by loading the photosensitizer Chlorin e6 (Ce6), thrombin (Thr), and AQ4N within the calcium phosphate nanocarrier via a simple one-pot method. In the acidic TME, TACC NPs could be degraded to release Thr and Ce6, resulting in the destruction of tumor vessels and consumption of intratumoral oxygen under laser irradiation. Therefore, the intratumoral hypoxia level could be significantly aggravated, further leading to the enhanced chemotherapeutic effect of AQ4N. With the guidance of in vivo fluorescence imaging, the TACC NPs exhibited excellent tumor embolization/photodynamic/prodrug synergistic therapeutic effects with good biosafety.